Evidence for the stability of ultrahydrous stishovite in Earth’s lower mantle - Lin, Yanhao (Proc Natl Acad Sci U S A, 2020)
The distribution and transportation of water in Earth’s interior depends on the stability of water-bearing phases. The transition zone in Earth’s mantle is generally accepted as an important potential water reservoir because its main constituents, wadsleyite and ringwoodite, can incorporate weight percent levels of H(2)O in their structures at mantle temperatures. The extent to which water can be transported beyond the transition zone deeper into the mantle depends on the water carrying capacity of minerals stable in subducted lithosphere. Stishovite is one of the major mineral components in subducting oceanic crust, yet the capacity of stishovite to incorporate water beyond at lower mantle conditions remains speculative. In this study, we combine in situ laser heating with synchrotron X-ray diffraction to show that the unit cell volume of stishovite synthesized under hydrous conditions is ∼2.3 to 5.0% greater than that of anhydrous stishovite at pressures of ∼27 to 58 GPa and temperatures of 1,240 to 1,835 K. Our results indicate that stishovite, even at temperatures along a mantle geotherm, can potentially incorporate weight percent levels of H(2)O in its crystal structure and has the potential to be a key phase for transporting and storing water in the lower mantle.